Aspek Moral dalam Karangan Siswa SD - Muhana Gipayana (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: Development of elementary students’ writing skills can be seen from writing style, attitude, cognitive, and moral aspects. The moral aspect can be analyzed by cumulative based moral development model instrument which is expressed by moral judgment physical characteristic, law, status, conventional, objective or motive, and abstract universal concept norms. Capacity of moral development which is expressed in upper class elementary schools students’ composition can be seen in the socionomic level, i.e. norms that can develop sense of tolerance to others. The development of norms of abstract universal concept and development of personal value system are not expressed yet.